Vertebrobasilar Artery Dolicoectasia: A Case Report - Özlem Buluz; Orkide Kutlu; Ayça Zeynep Kutlu; Hakan Selçuk (Turkish Journal of Internal Medicine, 2021)
Dolichoectasis is a dilative arteriopathy that can be seen in intracranial vertebral and basilar arteries in people with hypertension and advanced age. Although most cases are asymptomatic, cerebral ischemia, bleeding or compression may occur. The diagnosis of VBD was made by catheter angiography before; while MR angiography is the most sensitive imaging method today. In addition, differential diagnosis of aneurysm/other vascular problems, demyelinating diseases and space-occupying lesions can be made with MR imaging. Here, we aimed to report VBD because it is a rare condition in a hypertensive patient presenting with impaired balance.